C‐reactive protein/albumin ratio is a poor prognostic factor of esophagogastric junction and upper gastric cancer. Issue 2 (6th September 2018) - Kudou, Kensuke; Saeki, Hiroshi; Nakashima, Yuichiro; Kamori, Tomohiro; Kawazoe, Tetsuro; Haruta, Yasuhiro; Fujimoto, Yoshiaki; Matsuoka, Hiroya; Sasaki, Shun; Jogo, Tomoko; Hirose, Kosuke; Hu, Qingjiang; et al.
Abstract: Background and Aim: The C‐reactive protein (CRP)/albumin (Alb) ratio has been reported as a novel prognostic marker in several cancers. The objective of this study was to investigate the prognostic value of the CRP/Alb ratio in patients who underwent surgery for adenocarcinoma of the esophagogastric junction (AEG) and upper gastric cancer (UGC). Methods: Data for 144 patients who underwent surgery for AEG and UGC were reviewed. The CRP/Alb ratio, neutrophil–lymphocyte ratio, platelet–lymphocyte ratio, Glasgow Prognostic Score, and controlling nutritional status score were calculated, and the relationship between these biomarkers and postoperative prognosis was analyzed. Results: The optimal cutoff value of the CRP/Alb ratio was determined to be 0.1. According to the cutoff value of CRP/Alb ratio, patients were divided into two groups (CRP/Alb < 0.1, n  = 124; CRP/Alb ≥ 0.1, n  = 20). The 5‐year recurrence‐free survival and overall survival (OS) rates were significantly lower in the patients with the CRP/Alb ratio ≥ 0.1 than in those with the CRP/Alb ratio < 0.1 (recurrence‐free survival: 44.9% vs 77.9%, P  = 0.0011; OS: 43.4% vs 82.0%, P  < 0.0001). In the multivariate analyses, the N‐stage, and CRP/Alb ratio ≥ 0.1 were identified as independent predictive factors for OS in patients with AEG and UGC ( P  = 0.0061 and P  = 0.0439, respectively). Conclusions: The CRP/Alb ratio was strongly associated with poor prognosis in patients who underwent surgery for AEG and UGC.